Scrape-off layer ion temperature measurements at the divertor target during type III and type I ELMs in MAST measured by RFEA. (20th April 2016) - Elmore, S; Allan, S Y; Fishpool, G; Kirk, A; Thornton, A J; Walkden, N R; Harrison, J R
Abstract: In future nuclear fusion reactors high heat load events, such as edge-localised modes (ELMs), can potentially damage divertor materials and release impurities into the main plasma, limiting plasma performance. The most difficult to handle are type I ELMs since they carry the largest fraction of energy from the plasma and therefore deposit the largest heat flux at the target and on first wall materials. Knowing the temperature of the ions released from ELM events is important since it determines the potential sputtering they would cause from plasma facing materials. To make measurements of T i by retarding field energy analyser (RFEA) during type I ELMs a new operational technique has been used to allow faster measurements to be made; this is called the fast swept technique (FST). The FST method allows measurements to be made within the time of the ELM event which has previously not been possible with T i measurements. This new technique has been validated by comparing it with a slower average measurement previously used to make ion temperature measurements of ELMs. Presented here are the first T i measurements during Type I ELMs made at a tokamak divertor. Temperatures as high as 20 eV are measured more than 15 cm from the peak heat flux of an ELM, in a region where no inter-ELM current is measured by the RFEA; showing that ELM events cause hot ions to reach the divertor target far into the scrape off layer. Fast camera imaging has been used to investigate the type of ELM filaments that have been measured by the divertor RFEA. It is postulated that most of the ion temperatures measured in type I ELMs are from secondary ELM filaments which have not been previously identified in MAST plasmas.